Pelatihan pembuatan sabun dari minyak jelantah pada Kader PKK Desa Merembu - Subaidah, Windah Anugrah; Hajrin, Wahida; Pratiwi, Eskarani Tri; Ridwan, Sucilawaty (Universitas Mataram, 2024)
Indonesian people have a strong preference for food processed using cooking oil. However, the continuous reuse of cooking oil can pose health hazards and have negative environmental impacts if disposed of directly into the soil and waterways. Therefore, innovation is needed to process used cooking oil waste into a product with economic value. Used cooking oil used for cooking can be transformed into soap which is environmentally friendly and has economic value. Hence, this community service aims to reduce the volume of waste cooking oil and improve the local economy. One area in West Nusa Tenggara that has the potential for this product development is the village of Merembu. Out of 2084 families, 727 are still classified as poor. Therefore, there is a need for business opportunities to improve the economy in the village, one of which is by transforming waste cooking oil into soap products. Community service activities in Merembu Village were well received and received positive responses from Empowerment of Family Welfare (PKK) group in Merembu Village. The positive response is reflected in the results of the final evaluation carried out. This activity is a means for PKK group to increase their knowledge of the dangers and methods of processing used cooking oil so that it does not become a pollutant for the environment.